Microencapsulation of probiotic lactic acid bacteria using freeze-drying with isolated whey protein and trehalose as coating material [Mikroenkapsulasi bakteri asam laktat probiotik menggunakan pengeringan beku dengan protein whey isolat dan trehalosa sebagai material pelapis] - Parhusip, Adolf Jan Nexson (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Microencapsulation could be employed to coat bacteria with protective compounds to enhance their viability. The freeze-drying method uses low temperatures, thereby reducing heat damage. Bifidobacterium breve was used as a probiotic along with Streptococcus thermophilus and Lactobacillus bulgaricus, two common yogurt cultures. Yogurt, a nutrient-rich milk product, has the potential to be an effective probiotic carrier. This research aimed to examine how the freeze-drying process with varying ratios of coating materials affects the viability of the bacteria combination B. breve, S. thermophilus, and L. bulgaricus under acidic and bile salt conditions, as well as the microencapsulation efficiency and particle size. The treatments tested different ratios of whey protein isolate to trehalose as a coating (1:1, 1.5:1, 2:1, 2.5:1, 3:1). The 1:1 ratio yielded the best results, with lactic acid bacteria counts of 6.60 log colony/mL at pH 2.0, 6.84 log colony/mL at pH 3.0, 7.39 log colony/mL at pH 4.0, 7.47 log colony/mL at pH 5.0, 7.70 log colony/mL at pH 6.0, and 7.05 log colony/mL in a bile salt environment. This ratio demonstrated 107.96% microencapsulation efficiency and a particle size of 9.66 μm.